2003
DOI: 10.1074/jbc.m304016200
|View full text |Cite
|
Sign up to set email alerts
|

The Transforming Activity of Ski and SnoN Is Dependent on Their Ability to Repress the Activity of Smad Proteins

Abstract: ski and sno are members of the ski family of nuclear protooncogenes (1-3). Ski was originally identified as the transforming protein of the avian Sloan-Kettering retrovirus (v-Ski) (4, 5). The human cellular homolog c-ski and the closely related snoN were later cloned based on sequence homology to v-ski (1). The amino-terminal region of Ski is highly conserved among Ski family members, including v-Ski (Ͼ95% sequence identity) and SnoN (70% identity), whereas the carboxyl-terminal half of the molecule shows lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 60 publications
(80 reference statements)
3
104
0
1
Order By: Relevance
“…Although phosphorylation of R-Smads and accumulation of phosphorylated Smads in the nucleus are typical indicators of TGF-b and BMP stimulation, it is known that transcriptional corepressors, including c-Ski and SnoN, are overexpressed in some cancer cells, in which they inhibit TGF-b and BMP signaling through interactions with Smad complexes (He et al, 2003;Fukuchi et al, 2004). To study whether Smad-dependent transcriptional pathways were active in the bone metastasis, we used a functional imaging system using a xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…Although phosphorylation of R-Smads and accumulation of phosphorylated Smads in the nucleus are typical indicators of TGF-b and BMP stimulation, it is known that transcriptional corepressors, including c-Ski and SnoN, are overexpressed in some cancer cells, in which they inhibit TGF-b and BMP signaling through interactions with Smad complexes (He et al, 2003;Fukuchi et al, 2004). To study whether Smad-dependent transcriptional pathways were active in the bone metastasis, we used a functional imaging system using a xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…The R-Smad binding region has recently been reported to be located between amino acid residues 16 and 40 (Qin et al, 2002) or the N-terminal 23 amino acid residues (Wu et al, 2002) of c-Ski. Although Smad2/3 also binds the middle region of c-Ski (amino acid residues 335-490 or 241-441), the affinity of the middle region appears to be lower than that of the N-terminal region (Akiyoshi et al, 1999;He et al, 2003;our unpublished observation). We thus constructed a truncated mutant lacking the N-terminal 40 amino acid residues (⌬40) as well as a double mutant with ⌬40 and ARPG insertion and confirmed that the ⌬40 mutation caused loss of R-Smad binding.…”
Section: Lack Of Smad4 Binding Confers Tgf-␤/activin Selectivity To Cmentioning
confidence: 99%
“…Although the oncogenic mechanism of v-Ski is not fully understood, suppression of TGF-␤-induced growth inhibition is thought to be a part of the oncogenic properties of Ski proteins (He et al, 2003). v-Ski has a truncated structure in both the N-and C-termini of c-Ski; v-Ski lacks a 23-amino acid region from its N-terminus, and a 292-amino acid region from its C-terminus .…”
Section: Molecular Basis For the Loss Of Transforming Activity Of V-smentioning
confidence: 99%
See 2 more Smart Citations